2022
DOI: 10.1111/ajt.16843
|View full text |Cite
|
Sign up to set email alerts
|

Use of anti-spike monoclonal antibodies in kidney transplant recipients with COVID-19: Efficacy, ethnic and racial disparities

Abstract: Organ transplant recipients may not mount an adequate immune response to COVID‐19 infection and therefore may benefit greatly from passive immunization with anti‐spike monoclonal antibodies (mAbs), which have been shown to decrease hospitalization rates in the general outpatient population. We evaluated the efficacy of mAb therapy in decreasing hospitalizations or emergency room (ER) visits among kidney transplant recipients (KTR) with COVID‐19. We identified KTR with COVID‐19 between March 1, 2020 and April 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 20 publications
2
40
2
Order By: Relevance
“…The finding of mAb treatment disparities is consistent with previous studies. A single-center study of kidney transplant patients found that Black and Hispanic patients infected with SARS-CoV-2 were less likely to receive mAb and more likely to be hospitalized (5). The current study did not identify the underlying causes for the observed disparities.…”
Section: Discussioncontrasting
confidence: 58%
“…The finding of mAb treatment disparities is consistent with previous studies. A single-center study of kidney transplant patients found that Black and Hispanic patients infected with SARS-CoV-2 were less likely to receive mAb and more likely to be hospitalized (5). The current study did not identify the underlying causes for the observed disparities.…”
Section: Discussioncontrasting
confidence: 58%
“…This data confirms that timely and early administration of monoclonal antibodies is associated with a significantly lower risk of hospitalization. The providers should be aware of and address any possible disparities involving underrepresented populations when providing these potentially lifesaving options [35,42].…”
Section: Anti-sars-cov-2 Monoclonal Antibody In Solid Organ Transplan...mentioning
confidence: 99%
“…Accumulating evidence has demonstrated that neutralizing antibody, including casirivimab/imdevimab, bamlanivimab/etsevimab, and sotrovimab, are associated with lesser hospitalization duration and death rate for high-risk patients and SOTRs with mild-to-moderate COVID-19 [5,[14][15][16][17][18][19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with solid organ transplants, diabetes mellitus, cardiovascular disease, chronic obstructive pulmonary disease, and cancer have a worse prognosis after COVID-19 [3,4]. In particular, solid organ transplant recipients (SOTRs) are at high risk for severe COVID-19 due to comorbidities and immunosuppression [5]. Although the treatment for COVID-19 is limited, various combination therapies are explored, including remdesivir as an anti-viral agent, dexamethasone, tocilizumab, and baricitinib as an anti-in ammation agent [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation